Highly Charged, Cytotoxic, Cyclometalated Iridium(III) Complexes as Cancer Stem Cell Mitochondriotropics. Issue 57 (10th September 2018) - Laws, Kristine; Eskandari, Arvin; Lu, Chunxin; Suntharalingam, Kogularamanan
Abstract: The cancer stem cell (CSC) toxicity and mechanism of action of a series of iridium(III) complexes bearing polypridyl and charged 1‐methyl‐2‐(2‐pyridyl)pyridinium ligands, 1 –4 is reported. The most effective complex (containing 1, 10‐phenanthroline), 3, kills CSCs and bulk cancer cells with equal potency (in the micromolar range), indicating that it could potentially remove heterogenous tumour populations with a single dose. Encouragingly, 3 also inhibits mammopshere formation to a similar extent as salinomycin, a well‐established anti‐CSC agent. This complex induces CSC apoptosis by mitochondrial membrane depolarization, inhibition of mitochondrial metabolism, and intracellular reactive oxygen species (ROS) generation. To the best of our knowledge, this is the first study to investigate the anti‐CSC properties of iridium complexes. Abstract : Iridium mitochondriotropics : A series of iridium(III) complexes bearing polypridyl and charged 1‐methyl‐2‐(2‐pyridyl)pyridinium ligands, is reported and their anti‐cancer stem cell properties are described in detail. The highly charged, lipophilic compounds are shown to kill breast cancer stem cells by disrupting mitochondrial membrane potential and mitochondrial respiration.